First-aid manual for teachers - Medina Domínguez, Javier; Robles Carrascosa, Ana (Avances en Supervisión Educativa, 2010)
By Javier Medina Domínguez & Ana Robles (Teachers at Alpajés High School in Aranjuez, Madrid). Web2.0., Wiki, podcast, blogs,... You have most certainly come across any of these terms or have attended a talk between some so-called technological workmates. Perhaps you even once intended to become a member of this exclusive club and use these resources in your classroom.